Dynamics of mosque-based da’wah and its implications for the Diversity of muslim communities in Medan - Abdullah, Abdullah (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2023)
Purpose - This study aims to determine the dynamics of mosque-based da’wah and its implications for the diversity of society in the city of Medan.Method - This study used a qualitative-quantitative approach (mixed method) with a descriptive method. This study uses data sources in the form of primary and secondary, which are based on experience or literature review. Data collection techniques were carried out through interviews and observation. In data analysis techniques, researchers reduce data, present it, then conclude.Result – this study indicates that the preachers in Medan have approached the professional direction in preaching. The preachers can be said to have competence so that they can carry out their duties as rijalud da’wah properly.Implication - The preaching material delivered is generally still focused on the basic Islamic sciences, and a small part has started to develop da’wah material more broadly.Originality - The da’wah methods used by the preachers are very diverse; providing problem-solving offers on religious issues, building religious awareness, mastering social media da’wah strategies, and paying attention to the philosophy of da’wah (goals to be achieved), abilities and expertise (da’i background), sociology (situations and conditions), and psychology (pleasant thing).***Tujuan - Penelitian ini bertujuan untuk mengetahui dinamika dakwah berbasis masjid dan implikasinya terhadap keberagaman masyarakat di Kota Medan.Metode - Penelitian ini menggunakan pendekatan kualitatif-kuantitatif (mix method) dengan metode deskriptif. Penelitian ini menggunakan sumber data dalam bentuk primer dan sekunder, yakni berdasarkan pengalaman ataupun kajian literatur. Teknik pengumpulan data dilakukan dengan cara wawancara dan observasi. Pada teknik analisis data, peneliti melakukan reduksi data, menyajikannya, kemudian membuat suatu kesimpulan.Hasil - penelitian ini menunjukkan bahwa para da’i di Kota Medan telah mendekati kearah professional dalam berdakwah. Para da’i dapat disebutkan sebagai da’i yang memiliki kompetensi, sehingga mampu menunaikan tugas sebagai rijaluddakwah dengan baik.Implikasi - Materi dakwah yang disampaikan umumnya masih terfokus pada ilmu-ilmu dasar keislaman dan sebahagian kecil sudah mulai mengembangkan materi dakwah secara lebih luas.Orisinalitas - Metode dakwah yang digunakan oleh para da’i sangat beragam; memberikan tawaran problem solving isu-isu keagamaan, membangun kesadaran beragama, mengusai strategi dakwah media sosial, serta memperhatikan filosofi dakwah (tujuan yang kaan dicapai), kemampuan dan keahlian (latar belakang da’i), sosiologi (situasi dan kondisi), dan psikologi (hal yang disenenangi).